Integration of Artificial Intelligence Based Digital Media in Science Learning Activities to Improve Critical Thinking Skills of Vocational High School Students - Fitri Damayanti; Acep Musliman; Rino Anthony Stiawan; Andri Suryana; Samuel Amponsah (Universitas Syiah Kuala, 2026)
This study investigated the integration of Artificial Intelligence based digital media into Argumentation Driven Inquiry learning activities to enhance vocational high school students’ critical thinking and problem-solving skills in Jakarta. The research employed a mixed-methods design involving two vocational schools (SMK PGRI 16 and 20). Data was collected through pre- and post-assessments, classroom observations, and structured interviews with students, teachers, and parents. Digital media included adaptive AI-powered learning modules and interactive simulations designed to foster curiosity and collaborative argumentation. Quantitative results showed significant improvements in students' Critical Thinking Skills, with an average increase of 23% between the pre- and post-tests, whileqQualitative findings revealed that AI-based digital media improved motivation, fostered deeper engagement with IPAS concepts, and supported self-directed learning. Despite the positive outlook, challenges included limited infrastructure and uneven digital literacy among students. Overall, the integration of AI-driven digital media in ADI-based learning offers a promising pathway to strengthen Higher order Thinking Skills in vocational education